The shining (1980) [videorecording (DVD)] - Kubrick, Stanley; Nicholson, Jack; Duvall, Shelley, 1949-; Lloyd, Danny, 1973-; Crothers, Scat Man; Nelson, Barry, 1920-2007; Stone, Philip, 1924-2003; Turkel, Joe, 1927-; Jackson, Anne, 1925-2016; Burton, Tony; King, Stephen, 1947- (Warner Bros. Entertinment Inc., 2007)
A writer and his family are snowbound in a hotel and are haunted by either the hotel itself or the writer's dementia.